ASSESSING CROSS-CULTURAL ADAPTATION OF INTERNATIONAL STUDENTS IN IIUM - Hassan Radwan Jamal; Saodah Wok, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
In today’s world, many international students from other countries arriving at the host nation are exposed to a wide range of local cultures and values. Malaysia, being a multi-ethnic, multi-religious, and multi-cultural country, is put in a unique position that attracts many international students and foreigners alike. Regardless, many international students experience a clash of cultures between their own and the host’s culture, which if not dealt with could have detrimental effects on areas such as studies, social-circles, and self-esteem. Therefore, this study explored the challenges that both undergraduate and postgraduate international students of IIUM encounter when arriving in Malaysia. This study employed a quantitative research design, using the survey method with a questionnaire as the research instrument for data collection. In this study, students aged 21 years old and above were surveyed. This study was based on the theory of cross-cultural adaptation, using the U-curve model that displays each stage of adaptation every student goes through. The findings demonstrated that the cultural stage of adaptation had a positive relationship with the cultural stage of euphoria, the cultural stage of culture shock, and the cultural stage of adjustment. Based on the theory of cross-cultural adaptation as a guide, all the hypotheses were supported in which all relationships were found to be positive and significant.